The Influence of Lampung Natural Lime Temperature and Heating Time on The Physical Properties and Hardness of Hydroxy Products (HA) - Agus Hendriyanto (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
Hydroxyapatite (HA), a vital component for tissue and porous applications, holds promise in bone regeneration. Derived from calcium carbonate (CaCO3), it's essential for biocompatibility in human bone replacement. This study aims to harness Lampung Province's limestone as a raw material for HA synthesis, simulating human bone properties. Ball milling (2, 3, and 4 hours at 300 rpm) and sintering (600 °C, 800 °C, and 1000 °C for 2, 3, and 4 hours) were varied, with analyses encompassing FTIR, XRD, SEM-EDX, and Vickers hardness. Mountain branch limestone, comprising 97.43% CaCO3, serves as a suitable bone substitute. FTIR spectra of calcined lime powder exhibit PO43-peaks at 1025.45 cm1, Ca-O vibrations at 1413.59 cm1, and OH groups at 3030.33 cm1, mimicking commercial HA. XRD patterns closely resemble the commercial product, with a peak at 2 32.26°. SEM-EDX analysis at 1000 °C for 4 hours reveals a uniform microstructure. Among milling processes, 2-hour milling at 300 rpm exhibits the highest calcium and phosphate levels in EDX results. Vibration testing indicates peak hardness at 1000 °C and 4 hours of processing.